PENGARUH INFORMASI INVESTASI ONLINE DAN MEDIA SOSIAL TERHADAP KEPUTUSAN INVESTASI PADA INSTRUMEN REKSADANA GEN Z MAHASISWA UNIVERSITAS PALANGKA RAYA DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MEDIASI - Fransiska Tumanggor; Tesalonika Tesalonika; Najwa Hayati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The rapid development of digital technology has increased Generation Z's access to investment information through online platforms and social media. However, easy access to information does not necessarily lead to appropriate investment decisions without adequate financial literacy. This study aims to analyze the influence of online investment information and social media on mutual fund investment decisions among Generation Z students at Universitas Palangka Raya, with financial literacy serving as a mediating variable. This research employed a quantitative approach using a survey method. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that online investment information and social media do not directly influence investment decisions. However, both online investment information and social media have a positive and significant effect on financial literacy. Furthermore, financial literacy has a positive and significant effect on investment decisions. The indirect effect analysis reveals that financial literacy successfully mediates the relationship between online investment information, social media, and investment decisions. These findings demonstrate that financial literacy plays a crucial role in helping students process and evaluate investment information obtained from digital media before making investment decisions. Therefore, improving financial literacy is essential to encourage more rational and well-informed investment decision-making among Generation Z investors.